Whole Word Morphology Reloaded: The Case for a Semiotic Turn - Dasgupta, Probal (Język. Komunikacja. Informacja, 2019)
GP-WWM is a research programme that uses WWM (Whole Word Morphology) in morphology, Generative Phonotactics in phonology, and a domain delineation that equates the phonology module with automatic processes. In this paper, we advocate letting semiotically based mechanisms reshape the way WWM deploys its Word Formation Strategies. We propose LSSG (Language-Specific Semiotic Guidelines) packages, pitting our main proposal, the purely semiotics-driven Cohort Coherence Design for such a package, against a sketchily delineated Diglossic Equations Design.